Beyond immunoglobulin G: Dissecting the role of colostrum in programming early immune function in calves* - L. Rostoll-Cangiano; M. Cid de la Paz; J.F. Pierre (JDS Communications)
Adequate colostrum intake is essential for neonatal calf health and development, not only reducing disease incidence but also promoting accelerated growth, earlier reproductive maturity, improved first-lactation milk yields, and lower culling rates. Although these advantages might be partly attributed to antibody-mediated disease prevention, emerging evidence highlights the critical role of colostrum's bioactive components in programming postnatal development. Colostrum's nutrient and bioactive composition is uniquely tailored to meet the developmental needs of newborn calves. Compared with mature milk, colostrum contains higher concentrations of proteins, fats, vitamins, and minerals, along with an array of growth factors and bioactive molecules that exert a foundational influence on the adaptation to extrauterine life. A deeper understanding of how these colostrum bioactive components collectively influence calf health is important to improve colostrum management and pave the way for refined nutritional and care strategies to support calves during this critical developmental period. In this review, we explore the multifaceted role of bovine colostrum beyond transfer of passive immunity, focusing on its influence in modulating early microbial encounters and guiding neonatal immune development.